Streptococcus thermophilus Phages in Whey Derivatives: From Problem to Application in the Dairy Industry - Mariángeles Briggiler Marcó; Nicolás Machado; Andrea Quiberoni; Viviana Suárez (Viruses, 2022)
Fifteen samples of whey protein concentrate (WPC) were tested against 37 commercial Streptococcus thermophilus strains to detect infective bacteriophages. Seventy-three diverse phages were isolated from 12 samples, characterized by using DNA restriction patterns and host range analyses. Sixty-two of them were classified as cos, two as pac, and nine as 5093, according to PCR multiplex assays. Phage concentration was greater than 104 PFU/g for 25.3% of isolated phages. Seven phages showed an unusual wide host range, being able to infect a high number of the tested strains. Regarding thermal resistance, pac phages were the most sensitive, followed by cos phages, those classified as 5093 being the most resistant. Treatments at 85 °C for 5 min in TMG buffer were necessary to completely inactivate all phages. Results demonstrated that the use, without control, of these whey derivatives as additives in dairy fermentations could be a threat because of the potential phage infection of starter strains. In this sense, these phages constitute a pool of new isolates used to improve the phage resistance of starter cultures applied today in the fermentative industry.